The Influence of Clean Lifestyle and Healthy Environment Maintained by Mothers on The Incidence of Stunting in Maratua District, Berau Regency - Parli Prananda; Rusdi Rusdi; Ainur Rachman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Stunting is a major health problem in the Indonesian archipelago, such as in the Maratua Island District, due to limited sanitation and access to health services. This study aims to analyze the relationship between maternal hygiene practices and household environmental conditions with the incidence of stunting in toddlers. Using a quantitative analytical observational cross-sectional design, the population of all mothers of toddlers aged 0-4 years (n=54) was taken by total sampling. Data were collected through a PHBS questionnaire, environmental observations, and WHO anthropometric Z-scores, analyzed univariately and bivariately using the Spearman Rank test. The results showed that 100% of toddlers were stunted (75.9% were short, 24.1% were very short), but there was no significant relationship between maternal hygiene practices (ρ=-0.031; p=0.825) or the home environment (ρ=0.139; p=0.317) with stunting. Stunting is multifactorial, so the conclusion recommends integrated interventions including nutrition, sanitation, and socioeconomic factors for effective prevention in the archipelago.